(untitled) (Law, State and Telecommunications Review, 2023)
[Purpose] To characterize the evolution of the regulatory debate on interoperability and network access in the evolutionary course of the Internet. [Methodology] Based on bibliographical research on the academic publications of cyberlaw and study cases in the United States and Europe, the objectives and the role played by network access regulation are identified. [Findings] From little or no regulatory concern in the early beginning of the Internet, interoperability converts itself into a relevant issue from the identification of the power asymmetries of the network participants, some of them being able even to limit or prevent the free flow of information, then the concept of gatekeeper arises. With the reorientation of the bargaining powers of the Internet supply chain, greater attention has been given to the content and application layer. Despite the challenges inherent to the sustainability of highly prescriptive regulatory designs, guarantees of interoperability are fundamental to the free flow of ideas, data and information, capable of preserving a free, plural and open to innovation Internet.